Modulation of oral microbiota: a new frontier in exercise supplementation - Bescosa, R.; Brookes, Z.; Belfield, L.; Fernandez-Sanjurjo, M.; Casas-Agustench, P. (PharmaNutrition, 2020)
Research on the human microbiome has flourished over the last decade due to the essential role that bacterial communities have in host physiology and health. Recent studies have indicated that exercise is an important modulator of the composition and activity of the gut microbiome. However, microbiota is present throughout the whole gastrointestinal tract, the oral cavity being the first place where a large community of microorganisms is found. Recent evidence has established the first link between the oral microbiome and the physiological response to exercise, which opens a new way to explore host-microbiota interactions. The oral cavity is essential for many other physiological processes such as food digestion, the sensory experience of eating and palatability and immunity. Within the oral cavity, saliva is a key element for regulating all these functions as well as to protect the oral environment providing a lubricating mucoid secretion with organic and inorganic constituents. Here, we review what is known about the potential link between exercise and the oral microbiome including its role in oral health. We also discuss the effect of diet and the impact of pre and probiotics on the oral microbiome and their potential ergogenic effect.